2019
DOI: 10.3390/biomedicines7020027
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma and Micrografts Enriched with Autologous Human Follicle Mesenchymal Stem Cells Improve Hair Re-Growth in Androgenetic Alopecia. Biomolecular Pathway Analysis and Clinical Evaluation

Abstract: Platelet rich plasma (PRP) and Micrografts containing human follicle mesenchymal stem cells (HF-MSCs) were tried as a potential treatment for androgenetic alopecia (AGA). However, little to no work has yet to be seen wherein the bio-molecular pathway of HF-MSCs or PRP treatments were analyzed. The aims of this work are to report the clinical effectiveness of HF-MSCs and platelet-rich plasma evaluating and reviewing the most updated information related to the bio-molecular pathway. Twenty-one patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
121
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 66 publications
0
121
1
Order By: Relevance
“…By comparing gene expression between ADMSCs and WJMSCs at the single-cell level, we found that HVGs are largely overlapped between them (Additional file 3: Figure S6A). These shared HVGs include genes, such as HGF, FGF2, FGF7, VEGFA, TGFB2, IGF2, IGFBP3-7, CSF3, PDGFA, PTGES, and PTGS2, coding proteins which are involved in bio-molecular pathways that could promote cell proliferation, differentiation, and neo-angiogenesis and suppress apoptotic cues, to favor wound healing and hair regrowth processes [98,105,109]. Furthermore, functional enrichment analysis of HVGs from ADMSCs showed similar results as those from WJMSCs (Additional file 3: Figures S6B-G), though they exhibited distinct differentiation propensity (Additional file 3: Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing gene expression between ADMSCs and WJMSCs at the single-cell level, we found that HVGs are largely overlapped between them (Additional file 3: Figure S6A). These shared HVGs include genes, such as HGF, FGF2, FGF7, VEGFA, TGFB2, IGF2, IGFBP3-7, CSF3, PDGFA, PTGES, and PTGS2, coding proteins which are involved in bio-molecular pathways that could promote cell proliferation, differentiation, and neo-angiogenesis and suppress apoptotic cues, to favor wound healing and hair regrowth processes [98,105,109]. Furthermore, functional enrichment analysis of HVGs from ADMSCs showed similar results as those from WJMSCs (Additional file 3: Figures S6B-G), though they exhibited distinct differentiation propensity (Additional file 3: Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation procedures are not standardized yet and regenerative mechanisms are still the object of study due to their various growth factors (GFs). The effects of the GFs contained in AA-PRP and A-PRP in HG have been reported [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…To better explain the clinical results obtained by the use of minoxidil, finasteride, A-PRP, and HFSCs, it is necessary to report the most recent outcomes in hair density and hair count obtained for these treatments. In detail, in a recent study of Gentile et al [19], hair density improvement for A-PRP 23 weeks after the third infiltration (one infiltration was performed three times for 30 days each) was 28 ± 2% hairs/cm 2 compared with placebo (saline solution). In the same study, hair density improvement for HFSC treatment 23 weeks after the second infiltration (one infiltration was performed every 60 days for two times) was 29 ± 5% hairs/ cm 2 compared with placebo (saline solution) [19].…”
Section: Discussionmentioning
confidence: 92%
“…In detail, in a recent study of Gentile et al [19], hair density improvement for A-PRP 23 weeks after the third infiltration (one infiltration was performed three times for 30 days each) was 28 ± 2% hairs/cm 2 compared with placebo (saline solution). In the same study, hair density improvement for HFSC treatment 23 weeks after the second infiltration (one infiltration was performed every 60 days for two times) was 29 ± 5% hairs/ cm 2 compared with placebo (saline solution) [19]. In a study of Van Nestle et al [20], 212 males affected by AGA were selected in a randomized model to receive 1 mg finasteride daily (study group) or placebo (control group) for 48 Ws.…”
Section: Discussionmentioning
confidence: 92%